Normal Baru Pasca Covid-19 - Andrian Habibi (ADALAH, 2020)
AbstractHuman life throughout the world has changed. This change was due to the covid-19 virus which forced new conditions. In this case, globally social life has created a new order. Human life everywhere enters a room called the New Normal. This article wants to explain how the new normal picture is formed. A condition and / or social habits of the community or individual behavior that arises after covid-19 is completed.Keywords: Covid-19 and New Normal AbstrakKehidupan manusia di seluruh dunia berubah. Perubahan ini akibat virus covid-19 yang memaksa kondisi baru. Dalam hal ini, secara global kehidupan sosial tercipta suatu tatanan baru. Kehidupan manusia di mana pun memasuki ruang bernama Normal Baru. Artikel ini ingin menjelaskan bagaimana gambaran normal baru itu terbentuk. Suatu kondisi dan/atau kebiasaan sosial masyarakat atau perilaku individu yang muncul setelah covid-19 selesai.Kata Kunci: Covid-19 dan Normal Baru